Effects of board structure and corporate ownership on dividend payout : evidence from Singapore-listed firms. - Chen, Cindy. (2008)
This study investigates both the determinants of likelihood and the level of dividend payout. In addition, we look into the substitution and complementary effects of corporate governance structure in influencing the dividend payout of firms.